3D finite element modeling of selective laser melting for conduction, transition and keyhole modes. (March 2022) - Alexopoulou, Vasiliki E.; Papazoglou, Emmanouil L.; Karmiris-Obratański, Panagiotis; Markopoulos, Angelos P.
Abstract: Selective Laser Melting (SLM) consists one of the most widely used 3D printing methods, capable of producing metallic parts of high density and quality. During SLM, complex physical mechanisms and phenomena are taking place, affecting the overall process, thus, extensive relevant research is conducted in the recent years. Along with the experimental research that is carried out, different modeling methodologies have been proposed to simulate the process and to gain a better understanding, exploiting the capability to predict and optimize the process' results. The current paper presents a modeling methodology to simulate the formation of the melting pool during a single track in SLM, for conduction, transition and keyhole modes depending on the utilized Volumetric Energy Density (VED). A heat transfer model has been combined with deformed geometry to simulate the material vaporization, depending on the VED, since the material vaporization mechanism can be considered as a major importance parameter in the keyhole formation. To retain the generality and the simplicity of the model, only one coefficient that needs an estimation was adopted, namely, the atom recombination factor βR, which is directly correlated with the VED, while other parameters were defined based on analytical solutions and basic physics models. The accuracy of the model was validated through a "blind" comparison with experimental results from literature in terms of melting pool depth and Heat Affected Zone (HAZ) depth and width, with the simulation result being in high agreement with experimental ones. Finally, conclusion regarding the material vaporization rate and the evolution of the process in a more microscopic level were also deduced. Graphical abstract: Unlabelled Image Highlights: FEM model of the SLM process by coupling heat transfer with deformed geometry. Capable to predict and simulate the main modes of SLM (conduction/transition/keyhole). Melting pool geometry prediction and its unique features depending on the mode. Estimation of the material vaporization rate as a function of the process VED.